High‐temperature steam‐treatment of PBI, PEKK, and a PEKK‐PBI Blend: A solid‐state NMR and IR spectroscopic study. Issue 6 (27th October 2012) - Guenther, Johannes; Wong, Minhao; Sue, Hung‐Jue; Bremner, Tim; Blümel, Janet
Abstract Blends of polyaryletherketones (PAEK) with polybenzimidazole (PBI) are of commercial interest due to their improved upper service temperatures and wear properties when compared with the PAEK analogs examined to date. The retention of properties of the PBI component generally thought to be disadvantageous in more thermally or chemically aggressive environments is not well understood, nor are the specifics of interactions between the PBI and PAEK components in a melt or dry blend systems. In this initial investigation, focus is placed on the behavior and mechanism of polyetherketoneketone (PEKK)/PBI systems in contact with steam or condensed phase water. The goal is to understand the chemistry of the reaction, if any, upon exposure to steam as well as to examine the reversibility of moisture uptake of this material when exposed to liquid water or saturated steam. In this contribution, the pure polymer components and the PEKK‐PBI (60 : 40 wt %) blend are steam‐treated at 149°C (300°F) and 316°C (600°F). IR and solid‐state NMR spectroscopy are used to study chemical or morphological transformations of the polymers. All changes detectable by 13C cross‐polarization with magic angle spinning (CP/MAS) upon steam‐treatment are reversible, and not of a chemical nature, indicating that under the conditions of exposure used here no detectable chemical degradation occurs during steam exposure and with moisture uptake. The temporary water uptake of the samples, as studied by 1H wideline NMR and 13C T1 time measurements, leads to a change in the ratio of rigid versus mobile domains of the materials. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013